2003
DOI: 10.1017/cbo9780511840975
|View full text |Cite
|
Sign up to set email alerts
|

Vygotsky's Educational Theory in Cultural Context

Abstract: This 2003 book comprehensively covers all major topics of Vygotskian educational theory and its classroom applications. Particular attention is paid to the Vygotskian idea of child development as a consequence rather than premise of learning experiences. Such a reversal allows for new interpretations of the relationships between cognitive development and education at different junctions of the human life span. It also opens new perspectives on atypical development, learning disabilities, and assessment of chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Previous studies have shown that the parental style of immigrant parents from FSU is characterized by authority with less consideration of the child's wishes and emotional needs [9,30] . FSU immigrant's mothers consider themselves responsible for their children's developmental-educational processes and tend to create structured learning stimuli in an organized environment [9,31] . The developmental-educational approach in Soviet-Russian culture emphasizes the parent's role in modifying and adjusting the child's behavior from infancy [31] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the parental style of immigrant parents from FSU is characterized by authority with less consideration of the child's wishes and emotional needs [9,30] . FSU immigrant's mothers consider themselves responsible for their children's developmental-educational processes and tend to create structured learning stimuli in an organized environment [9,31] . The developmental-educational approach in Soviet-Russian culture emphasizes the parent's role in modifying and adjusting the child's behavior from infancy [31] .…”
Section: Discussionmentioning
confidence: 99%
“…FSU immigrant's mothers consider themselves responsible for their children's developmental-educational processes and tend to create structured learning stimuli in an organized environment [9,31] . The developmental-educational approach in Soviet-Russian culture emphasizes the parent's role in modifying and adjusting the child's behavior from infancy [31] . Although the immigrant mothers participating in the current study have lived in Israel for about 14 years, it is likely that some of the Soviet-Russian norms regarding infant care have endured.…”
Section: Discussionmentioning
confidence: 99%
“…The study is based on the Reading Motivation Theory [2], Perspective on Cognitive Development [16], and the Self-determination Theory [5]. These theories stated that intrinsic motivation of the learner coupled with self-determination would definitely result to higher cognitive development.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Firstly, by mean of interrelation with others and then integrated into the human mental formation. All function in the child's cultural advancement happens twice: first, on the social level and then later on the personal level (Kozulin, 2003;Simons et al, 2000). This conceptual description mean at the social level, child's mental cognition happen as a result interaction with people in the community (inter-psychology) and on the personal level mean incognito within the child (intra-psychology).…”
Section: Situated Learning Theorymentioning
confidence: 99%